HUBUNGAN TERPAAN WEB SERIES “SORE” DENGAN NIAT BELI TROPICANA SLIM STEVIA PADA MASYARAKAT DENPASAR - Eriyanti, Andiana Dwi; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT YouTube is the most favorite medium of view. The hgh traffic of YouTube visitors becomes the main attraction for companies to advertise in it. Web series is one of the forms of internet viewing on YouTube. Web series with soft selling technique seeks to create the impression and appeal emotionally so that a brand can be remembered through the terms of stories brought. The web series "Sore" is a web-series of advertised ads and has been watched by over 1 million viewers and was awarded as the Best Branded Video Content of the Year in XYZ Day 2018. The "Sore" web series was created as a method to introduce Tropicana Slim Stevia widely to the public. Basically the essence of advertising activity is to arouse a continuing intention on consumer action. The purpose of this study is to explain the exposure relationship web series "Sore" with the intention to buy Tropicana Slim Stevia on Denpasar Society. This study uses associative quantitative method. The sampling technique used in this research is non-probability sampling with purposive sampling method. The data is obtained by distributing questionnaires. Data analysis technique used in this research is test of construct validity, Cronbach Alpha technique reliability test and correlation test using Pearson Product Moment Correlation technique. The results show that there is a relationship between web exposure series "Sore" with the intention to buy Tropicana Slim Stevia on Denpasar Society. The direction of the relationship between exposure variable web series "Sore" with the intention to buy Tropicana Slim Stevia on Denpasar society depicted the same direction, which means themore people of Denpasar experienced web series "Sore", then the intention of buying of Denpasar people in Tropicana Slim Stevia will be higher. Based on these results, a web series with emotional appeal can be an option for ad producers to produce ads. Keywords: Advertisement, Exposure, Intention, "Sore" Web Series, Tropicana Slim Stevia